The Eternal Dilemma: to Translate, or not to Translate? Approaches and Positions - Salmeri, Claudio (Respectus Philologicus, 2017)
The phenomenon of translatability is an incredibly interesting translation problem, the subject of eternal disputes and discussions, which probably will never be definitively settled. Translatability is only a theoretical ideal, which, in fact, only corresponds to different degrees of approximation. Untranslatability is caused by the differences in the construction of language systems and the presence of different types of terms, words, common phrases and collocations related to specific socio-cultural phenomena in respective languages. The translatability of statements is also hindered by allusions of language and particular erudite manners of poetic text organisation, used for expressive and aesthetic language-specific sound values and semantic associations. Thus, the translatability of literature, and especially poetry, is particularly limited. The purpose of this article is to debate the problem of (un)translatability and to define its limits. The article is an attempt to discuss the fundamental questions of when the independence and freedom of manoeuvre of a translator reach their limits and whether a text should be translated or left in the original language.
Keywords: translatability; untranslatability; limits; culture; language